From Cosquín to San Antonio. Summer festivals and identitarian discourses (Revista Argentina de Musicología, 2020)
The aim of this paper is to study the relationship between four festivals that take place in Cordoba (Argentina) and have been important in the construction of identitarian narratives which, though different, are deeply interrelated. My purpose is to demonstrate that although each one of these events can be seen as unique, all of them are part of the same system stemming from the same social process; therefore their singularities are better understood by thinking in their relationship. I am referring to the Cosquín National Folklore Festival, La Falda Argentinian Contemporary Music Festival, Cosquín Rock Festival and the San Antonio de Arredondo National Culture Encounter. Each of them has become an annual rite with its center on popular music in two variants that have gained legitimation in Argentina with the passing of time: Rock and Folklore. The particularities of the analyzed festivals, but also their deep relationships, are better understood when related to the fundamental place of those two fields of popular music in the symbolic struggles to shape national identity.